The Development and the Growth Features of Sprouts of Malus Orientalis Uglitzk.Species Introduced in Absheron - Ceyran Najafova; Aynur Arabzade; Aygun Huseynova (International Journal of Secondary Metabolite)
Apple is cultivated in most of the temperate regions due to the fruit’s quality, its easiness to propagate, and its natural aptitude to bear. Malus classifications differ primarily in the taxonomic level at which infrageneric groupings of species are recognized. Object of the study was oriental apple (Malus orientalis Uglitzk) from Azerbaijan flora which was introduced to Absheron. The conducted experiments showed that the first sprouts of the seeds of the Malus orientalis sown in autumn were observed in the third decade of March. The first embryo roots which gives start to the main roots begin growth in germinal period before the ontogenesis. Thus, experiments have shown that Malus orientalis specie have normal growth in the ontogenesis initial development - germinal stage and it can be used as a perspective species for greening of Absheron.